The strategy of persuasion in the discourse of religious reference A study in the rhetoric of the perlocutionary effect - إسماعيل عسكر حيدر (Journal of College of Education, 2022)
This research aims to demonstrate the impact of the discourse of Religious reference on the listeners, their attitudes, and their behavior, starting from the fact that persuasion is an inherent feature of the speech in its function and effectiveness. And get him to act. Because of the importance of the goal of the speech and its reflection on the recipients, the speaker invests the means that allow him to appear in an appearance that brings him the confidence of the listeners (reporting rules), to work to move their passions and control their will and direct them (the rules of politeness), and then achieve the desired goal persuasion